Body issues, sexual satisfaction, and relationship status satisfaction in long‐term childhood cancer survivors and healthy controls. Issue 2 (8th May 2015) - Lehmann, Vicky; Hagedoorn, Mariët; Gerhardt, Cynthia A.; Fults, Marci; Olshefski, Randal S.; Sanderman, Robbert; Tuinman, Marrit A.
Abstract: Objective: Research on body image and sexual satisfaction after adult onset cancer has shown significant and lasting impairments regarding survivors' sexuality and romantic relationships. However, knowledge about these topics and their associations in adult survivors of childhood cancer is largely lacking. Methods: Participants completed web‐based questionnaires concerning body image, body dissociation, sexual satisfaction, and relationship status satisfaction (i.e., satisfaction with either being in a relationship or being single). Survivors ( n = 87) and controls ( n = 87) were matched on age and gender, with a mean age of 27 years (range: 20–40). Survivors were most often diagnosed with leukemia (46%), at an average of 16 years prior to study participation (range: 6–33 years). Results: Similar numbers of survivors and controls were single ( n = 24/31), in a committed relationship ( n = 33/23), or married ( n = 30/33). Survivors and controls reported comparable levels of body image, body dissociation, sexual experiences, and sexual and status satisfaction ( d = 0.15–0.28). Higher status satisfaction was associated with being in a relationship (compared with being single, β = 0.439), more positive body image ( β = 0.196), and higher sexual satisfaction ( β = 0.200). Conclusions: Adult survivors of childhood cancer were comparable to healthy peers regarding views of their bodies and psychosexual development, which was unexpected. Independent of whether people experienced cancer or not, their status satisfaction was associated with their relationship status, body image, and sexual satisfaction. Future research should explore why sexual and body problems are identified after adult onset cancer, whereas this seems to be less of a problem in childhood cancer survivors. Copyright © 2015 John Wiley & Sons, Ltd.